Social psychology and human nature - Baumeister, Roy F.; Bushman, Brad J. (Belmont, CA : Thomson Higher Education, 2008)
You are a member of a social world on a planet containing about 7 billion people. This social world is filled with paradox, mystery, suspense, and outright absurdity. Explore how social psychology can help you make sense of your own social world with this engaging and accessible book. Roy F. Baumeister and Brad J. Bushman$1 (Bs SOCIAL PSYCHOLOGY AND HUMAN NATURE can help you make sense of the always fascinating and sometimes bizarre and baffling diversity of human behavior-and it$1 (Bs also just plain interesting to learn about how and why people act the way they do.s
The Mission and the Method -- Culture and Nature -- The Self -- Behavior Control: The Self In Action -- Social Cognition -- Emotion and Affect -- Attitudes, Beliefs, and Consistency -- Prosocial Behavior: Doing What's Best for Others -- Aggression and Antisocial Behavior -- Close Relationships: Passion, Intimacy, and Sexuality -- Prejudice and Intergroup Relations -- Social Influence and Persuasion -- Groups -- Module A: Applying Social Psychology to Consumer Behavior -- Module B: Applying Social Psychology to Health -- Module C: Applying Social Psychology to Law -- Module D: Applying Social Psychology to the Environment -- Module E: Applying Social Psychology to the Workplace (available online through Thomson Custom Solutions).
Includes bibliographical references and indexes.
1
Keywords: Mission and the Method; Prosocial Behavior; Social Cognition; Culture and Nature; Behavior Control; Social psychology; Human behavior